The effects of financial literacy, accounting information, risk perception and herding behavior on investment decision - Gustiarum, Tetri; Kusumawardhani, Indra (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2023)
Based on data from KSEI, since 2019 the number of investors in Indonesia has increased significantly, known from the increase in the number of Single Investors Identification (SID). However, the level of financial literacy in Indonesia is still low. They indicated that people's understanding and knowledge of financial products is still need to be improved. The current study aims to assess the effect of financial literacy, accounting information, risk perception, and herding behavior on investment decisions. This research used quantitative techniques using questionnaires distributed to students of the accounting department at Veteran National Development University Yogyakarta, Indonesian Islamic University, and STIE YKPN Business School. This research used 70 respondents with a convenience sampling approach and multiple linear regression for analyzing the hypothesis. The result showed that financial literacy, accounting information, and herding behavior affect investment decisions. On the other hand, risk perception does not influence an investment decision